Development of the Indonesian Government's Digital Transformation - Sandra Willia Gusman (Dinasti Publisher, 2024)
Digital transformation has been the center of attention in efforts to modernize government in Indonesia in the last decade. This article documents the evolution and impact of the Indonesian government's digital transformation initiatives from 2010 to 2024. The Indonesian government has taken significant steps in encouraging the adoption of information and communication technology (ICT) to improve administrative efficiency, increase openness, and provide easier and faster access to public services. Key initiatives include the development of an e-government platform that provides online services from various government departments and agencies, as well as the implementation of an integrated data management system to improve evidence-based decision-making. In addition, Indonesia has also moved towards further digitalization by utilizing big data to formulate public policies that are more effective and responsive to the needs of the community. The national digital infrastructure being developed, such as the Palapa Ring, is an important foundation in supporting equitable internet connectivity across the country, facilitating digital inclusion in remote and urban areas. However, this digital transformation process is also faced with a number of challenges, including data security, technology accessibility in remote areas, and the readiness of human resources to adopt new technologies. This article also highlights the government's efforts to build people's capacity to utilize digital technology effectively through training and education programs. Overall, the Indonesian government's digital transformation has had a significant impact in improving administrative efficiency and transparency, as well as expanding access to public services. This article concludes by evaluating the opportunities and challenges ahead, as well as the broader implications of digital transformation on public participation and inclusive economic growth in this digital era.